2020
DOI: 10.1186/s13741-020-00170-4
|View full text |Cite
|
Sign up to set email alerts
|

Markedly increased risk of postoperative bleeding complications during perioperative bridging anticoagulation in general and visceral surgery

Abstract: Background Increasing numbers of patients receiving oral anticoagulants are undergoing elective surgery. Low molecular weight heparin (LMWH) is frequently applied as bridging therapy during perioperative interruption of anticoagulation. The aim of this study was to explore the postoperative bleeding risk of patients receiving surgery under bridging anticoagulation. Methods We performed a monocentric retrospective two-arm matched cohort study. Patients that received perioperative bridging anticoagulation were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…Prior to elective surgical procedures, the anticoagulative drugs are usually discontinued within an adequate time lag before surgery. However, due to the nature of the conditional limited time frame of deceased organ donation, the timely discontinuation of anticoagulative drugs is often not feasible [ 38 ]. In this context, the optimal timepoint for the postoperative resumption of anticoagulative medication following kidney transplantation is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…Prior to elective surgical procedures, the anticoagulative drugs are usually discontinued within an adequate time lag before surgery. However, due to the nature of the conditional limited time frame of deceased organ donation, the timely discontinuation of anticoagulative drugs is often not feasible [ 38 ]. In this context, the optimal timepoint for the postoperative resumption of anticoagulative medication following kidney transplantation is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…A substantial number of patients with colorectal cancer are already bleeding from the underlying tumour before surgery, and major bleeding complications might increase after major abdominal surgery in patients receiving therapeutic dosing of an anticoagulant. 18 Furthermore, other dosing regiments have already been assessed by TILT (intermediate dosing of tinzaparin 100 IU/kg, once a day for 12 weeks) and NVALT-8 (two weeks of therapeutic dosing then 14 weeks on intermediate dosing) and showed no benefit. 16 17 The PERIOP-01 trial used tinzaparin as an early adjuvant treatment starting from the day of surgery until day 56.…”
Section: Discussionmentioning
confidence: 99%
“…Prophylactic dosing of tinzaparin was used in the PERIOP-01 trial because therapeutic dosing could have a higher risk of bleeding complications in the perioperative setting. A substantial number of patients with colorectal cancer are already bleeding from the underlying tumour before surgery, and major bleeding complications might increase after major abdominal surgery in patients receiving therapeutic dosing of an anticoagulant 18. Furthermore, other dosing regiments have already been assessed by TILT (intermediate dosing of tinzaparin 100 IU/kg, once a day for 12 weeks) and NVALT-8 (two weeks of therapeutic dosing then 14 weeks on intermediate dosing) and showed no benefit 1617.…”
Section: Discussionmentioning
confidence: 99%
“…89 Concerns have been expressed on the safety of perioperative bridging for VTE prevention. 90 A recent multicenter trial confirmed that bridging or monitoring preoperative coagulation function is not necessary for those on DOACs undergoing elective surgery. 91 Other studies on geriatric hip fracture patients have also demonstrated that expediting surgery in the presence of DOAC without bridging does not lead to worse outcomes.…”
Section: Uncertainties With Bridging Anticoagulation and Anticoagulan...mentioning
confidence: 99%